Hypersonic similitude for planar wedges - Crasta, Asha; Khan, Sher Afghan (IAEME Publications, 2014)
A similitude has been obtained for a planar wedge with attached bow shock at high incidence in hypersonic flow. A strip theory in which flow at a span wise location is two dimensional developed by Ghosh is been used. This combines with the similitude to lead to a piston theory which gives closed form of solutions for unsteady derivatives in pitch. Substantially the same results as the theory of Liu and Hui are obtained with remarkable computational ease for some special cases. Effects of wave reflection and viscosity have not been taken into account.